Design An Irrigation System For Vegetable Farming Suitable For Malaysia Environment - idris, ahmad fu'ad; Anak Yunos Allie, Ericson Jawi (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The objectives of this project is to design an irrigation system for chili farmings suitable for Malaysia environment. This system used only one pump to operate where the pump only pumps the water from the river to the tank, and potential energy is used to irrigate the plant. Standard design process by G. E Dieter was used as the methodology of this project. As a result the drip irrigation system has been successfully designed. The system consist of the centrifugal pump, water tank and structural support, piping system, and support system. The pump used produce flow rate of 500 l/min and max head of 22 m, the tank size is 4000 liter, the number of chilli plant is 3700, and the structure height for tank is 5 meter. The pump is operating for 10 minutes per day. The total cost estimation for this project is RM 7691.90 and the Return Of Investment (ROI) for this system is 6 months period during first harvesting seasons.